Laws of the oxidation of carbon isotopes in plasma processes under magnetic field; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Khan V. A. Valery Alekseevich; Makarevich S. V. (2016, 2016)
Title screen